Aplikasi SIG Berbasis Desktop Untuk Sebaran Lokasi Usaha Pertambangan di Kabupaten Wonogiri - Annisaa Cahyaningsih; Arief Laila Nugraha; Hani'ah . (Departement Teknik Geodesi Universitas Diponegoro, 2014)
An accurate and up-to-date information or data concerning with mining trade in a certain area, is urgently needed by the local government because, based on such information, steps for making decisions about mining trade management policy could be facilitated. In addition, such an information will also be very helpful for businessmen as well practitioners interested or involving actively in the management of mining trade.To get the information of the distribution of mining trade locations GIS mapping is done by using GPS navigation and supported by the attributes data of mining trade such as a kind of mining trade permit, the locations, the type of mineral, the name of the owner, and so on. Next is making database from spatial and attribute data using MapInfo 10.0 software and presented in the form of application using Visual Basic 6.0 software. From the three methods mention above, it can be obtained the complete information about the distribution of mining trade locations.The result obtained from the analysis of mining trade in Wonogiri Regency there are 91 mining trade, 16 Mining Permit (IUP) and 75 Mining Permit for the Society (IPR) which is spread in 14 districts. The final result which is presented is in the form of desktop GIS application that can be used by the user in order to get the complete data of mining trade easily.Keywords: Mining Trade, GIS (Geographics Information System) , GIS Application